2015
DOI: 10.1016/j.pmrj.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Inpatient Rehabilitation in Patients With Simultaneous Bilateral Total Knee Arthroplasty

Abstract: After undergoing simultaneous bilateral TKA, patients demonstrate functional gains when admitted to inpatient rehabilitation facilities based on FIM gains and FIM efficiency scores; 8.5% of patients in this cohort required transfer to an acute care facility as a result of complications during inpatient rehabilitation, and 93.6% of patients were discharged home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…A total of 47 studies were identified relating to complications ( 2 , 17 , 25 69 ). Studies were conducted across a variety of international healthcare settings, including North America ( n = 22) ( 17 , 27 , 31 , 33 , 36 38 , 40 , 42 , 44 46 , 50 , 51 , 54 , 59 , 60 , 62 66 ), Europe ( n = 9) ( 26 , 29 , 34 , 35 , 43 , 49 , 52 , 55 , 69 ), Asia ( n = 11) ( 28 , 41 , 47 , 48 , 53 , 56 58 , 61 , 67 , 68 ) and Oceania ( n = 5) ( 2 , 25 , 30 , 32 , 39 ). Study cohorts included general rehabilitation ( 2 , 25 , 44 , 47 , 51 , 56 , 60 , 65 ) and rehabilitation following: cerebrovascular accident (CVA) ( 17 , 26 , 28 , 30 , 35 , 36 , 38 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 47 studies were identified relating to complications ( 2 , 17 , 25 69 ). Studies were conducted across a variety of international healthcare settings, including North America ( n = 22) ( 17 , 27 , 31 , 33 , 36 38 , 40 , 42 , 44 46 , 50 , 51 , 54 , 59 , 60 , 62 66 ), Europe ( n = 9) ( 26 , 29 , 34 , 35 , 43 , 49 , 52 , 55 , 69 ), Asia ( n = 11) ( 28 , 41 , 47 , 48 , 53 , 56 58 , 61 , 67 , 68 ) and Oceania ( n = 5) ( 2 , 25 , 30 , 32 , 39 ). Study cohorts included general rehabilitation ( 2 , 25 , 44 , 47 , 51 , 56 , 60 , 65 ) and rehabilitation following: cerebrovascular accident (CVA) ( 17 , 26 , 28 , 30 , 35 , 36 , 38 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly reported complications were infections, and non-infectious neurological alterations. Infectious complications were identified in 26 studies, with UTIs, pneumonia and cellulitis reported as the most common ( 17 , 26 – 28 , 31 , 34 36 , 38 , 41 , 46 48 , 51 53 , 55 , 57 – 59 , 61 , 64 , 66 69 ). Six studies noted infection to have occurred in over half of the study population ( 26 , 51 , 53 , 55 , 59 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can effectively relieve knee joint pain, recover knee joint function, and improve the patients' quality of life. [4][5][6] Due to the increasing population of elderly, the patients suffer from knee joint diseases increased and the application of TKA has also become mature than before. [7][8][9] The curative effect of TKA is related not only to the type of prosthesis, the amount of annual operation, appropriate osteotomy, and proper soft tissue balance but also to perioperative nursing care.…”
Section: Introductionmentioning
confidence: 99%